Angry Animals - Arnold, Nick (Horrible Science, 2008)
Science with the squishy bits left in! Take a walk on the wild side with Angry Animals Dare you discover: * who made false teeth for an elephant? * where you can find dragons with bad breath? * which scientist ate a poisonous snake for dinner? If you think you can stomach the sick side of Science, then read on as we go on the hunt for the cruellest creature of them all. Get to grips with gruesome grizzly bears, wolf down some facts about, er, wolves and snap up some savage shark stories. With fantastic fact files, quirky quizzes and crazy cartoons, Angry Animals is a book to sink your teeth into! Science has never been so horrible!